2020
DOI: 10.1111/aji.13362
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of systemic and uterine endometrial immune populations in patients with endometriosis

Abstract: Problem: Endometriosis is defined as growth of endometrial tissue in ectopic locations; it is associated with infertility and chronic pain and affects ~12% of reproductiveaged women. Although inflammation is known to play a key role in endometriosis, knowledge related to immune phenotypes associated with this disease is lacking. This study aimed to characterize immune profiles in patients with endometriosis, to assess inflammatory mediators, to and determine if surgical and/or hormonal therapies restore immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
4
8
0
Order By: Relevance
“…Le et al have recently reported an increased accumulation of Th17 cells and reduction in Treg cells in the peripheral circulation and ectopic endometrial tissue in patients with endometriosis, that seemed to be mitigated by hormone therapy but not by surgical removal of ectopic lesions. 40 All these previous studies support our findings that the low Treg and concurrent high Th17 cell phenotype is potentially responsible for the unsuccessful conception status in the subfertile patients with concurrent endometriosis, even after laparoscopic removal of ectopic lesions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Le et al have recently reported an increased accumulation of Th17 cells and reduction in Treg cells in the peripheral circulation and ectopic endometrial tissue in patients with endometriosis, that seemed to be mitigated by hormone therapy but not by surgical removal of ectopic lesions. 40 All these previous studies support our findings that the low Treg and concurrent high Th17 cell phenotype is potentially responsible for the unsuccessful conception status in the subfertile patients with concurrent endometriosis, even after laparoscopic removal of ectopic lesions.…”
Section: Discussionsupporting
confidence: 88%
“…Interleukin-17 (IL-17) is significantly higher in the peritoneal fluid of patients with minimal/mild stage endometriosis as compared to those with moderate/severe stage of disease. 41,42 Other studies have also shown abnormal serum 40 and peritoneal fluid 42 T-cell related cytokine levels in patients with endometriosis. IL-17 acts through the induction and expression of other pro-inflammatory cytokines and chemokines, 37 which mediate immune cell infiltration, angiogenesis and maintenance of endometriotic lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammatory Th17 cells are derived from the CD4 lineage of T cells that secrete interleukin-17 (IL17s), IL21, IL22 and express the RAR-related orphan receptor gamma transcription factor (RORγt), to activate cytotoxic CD8 + T cells. Plasma and peritoneal fluid levels of IL-17 are elevated in endometriosis patients and we, along with others, have reported that Tregs and Th17 immune cell populations contribute to the systemic and tissue specific inflammatory profile of patients with endometriosis 13 , 14 . Briefly we found low levels of peripheral Tregs, greater Th17 cell populations and an increase in the Th17/Treg ratio, indicative of systemic inflammation 14 .…”
Section: Introductionsupporting
confidence: 68%
“…Plasma and peritoneal fluid levels of IL-17 are elevated in endometriosis patients and we, along with others, have reported that Tregs and Th17 immune cell populations contribute to the systemic and tissue specific inflammatory profile of patients with endometriosis 13 , 14 . Briefly we found low levels of peripheral Tregs, greater Th17 cell populations and an increase in the Th17/Treg ratio, indicative of systemic inflammation 14 . We also reported that Tregs and Th17 localizations were enhanced within the ectopic endometrial implant, which promotes lesion development via induce angiogenesis 14 .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation